Assessment of Dental and Medical School students on the awareness of Oral Cancer - Pintor, Fernanda Emetério; Alves, Maria Luisa Maciel (Journal of Oral Diagnosis, 2022)
Oral cancer (OC) is a public health problem due to its high prevalence in the world po- pulation. Due to its late diagnosis, this pathology has been causing many sequelae for the patient and constitutes a risk of death when treated in advanced stages. One of the main aggravating factors is the difficulty in its early identification, both by health professio- nals and the population, since there are no explicit symptoms in the initial stages or the changes are often like other oral lesions, such as ulcers. Thus, they can go unnoticed by the individual and even by a health professional. This study evaluated the level of kno- wledge about OC in medical and dental students at the University of Santo Amaro. The study was carried out through a questionnaire with 38 (thirty-eight) questions. With that, we established a comparative parameter between both courses to show if the students were well prepared to deal with oral and oropharyngeal cancer. The survey also aimed to show how oral health is being neglected within medicine, making future physicians feel unprepared to care for their patients.